Proceedings of the 28th International Conference on Computational Linguistics 2020
DOI: 10.18653/v1/2020.coling-main.375
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Pure Character-Based Neural Machine Translation: The Case of Translating Finnish into English

Abstract: Recent work has shown that deeper character-based neural machine translation (NMT) models can outperform subword-based models. However, it is still unclear what makes deeper character-based models successful. In this paper, we conduct an investigation into pure character-based models in the case of translating Finnish into English, including exploring the ability to learn word senses and morphological inflections and the attention mechanism. We demonstrate that word-level information is distributed over the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Domingo and Casacuberta [11] evaluated word-based and character-based MT approaches, finding character-based to be more suitable for this task and that SMT systems outperformed NMT systems. Tang et al [53], however, compared many neural architectures and reported that the NMT models are much better than SMT models in terms of character error rate (CER). Finally, Hämäläinen et al [22] evaluated SMT, NMT, an edit-distance approach, and a rule-based finite state transducer and advocated for a combination of these approaches to make use of their individual strengths.…”
Section: Related Workmentioning
confidence: 99%
“…Domingo and Casacuberta [11] evaluated word-based and character-based MT approaches, finding character-based to be more suitable for this task and that SMT systems outperformed NMT systems. Tang et al [53], however, compared many neural architectures and reported that the NMT models are much better than SMT models in terms of character error rate (CER). Finally, Hämäläinen et al [22] evaluated SMT, NMT, an edit-distance approach, and a rule-based finite state transducer and advocated for a combination of these approaches to make use of their individual strengths.…”
Section: Related Workmentioning
confidence: 99%
“…It provides an insight into the fact that how well a model has learned the specified linguistic property. Several linguistic features have been analysed to extract different properties like Morphological, syntactic and semantic (Voita and Titov, 2020;Tang et al, 2021). It is based on the premise that if there is more task relevant information is learned by the model then it is going to perform better on the presented task.…”
Section: Probingmentioning
confidence: 99%
“…Character-level neural machine translation (Ling et al, 2015;Lee et al, 2017;Cherry et al, 2018;Gao et al, 2020) tokenizes the source sentence and target sentence according to characters, thereby gaining advantages over subword-level neural machine translation in some specific aspects, such as avoiding out-of-vocabulary problems (Passban et al, 2018) and errors caused by subword-level segmentation (Tang et al, 2020). In terms of translation quality, the character-level MT is still difficult to compare with the subword-level MT.…”
Section: Char-level Simultaneous Translationmentioning
confidence: 99%